2008
DOI: 10.1109/jsac.2008.081210
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Acoustic Networks: Channel Models and Network Coding Based Lower Bound to Transmission Power for Multicast

Abstract: Abstract-The goal of this paper is two-fold. First, to establish a tractable model for the underwater acoustic channel useful for network optimization in terms of convexity. Second, to propose a network coding based lower bound for transmission power in underwater acoustic networks, and compare this bound to the performance of several network layer schemes. The underwater acoustic channel is characterized by a path loss that depends strongly on transmission distance and signal frequency. The exact relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Together with the studies in terrestrial radio networks, the interest in study of underwater networks has been growing, due to recent advances in acoustic communication technology [15][16][17][18]. In underwater acoustic communication systems, both bandwidth and received signal power are severely limited owing to the exponential (rather than polynomial) path-loss attenuation with long propagation distance and the frequency-dependent attenuation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the studies in terrestrial radio networks, the interest in study of underwater networks has been growing, due to recent advances in acoustic communication technology [15][16][17][18]. In underwater acoustic communication systems, both bandwidth and received signal power are severely limited owing to the exponential (rather than polynomial) path-loss attenuation with long propagation distance and the frequency-dependent attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the system throughput is affected by not only the transmission distance but also the useful bandwidth. Based on these characteristics, network coding schemes [17,19,20] have been presented for underwater acoustic channels, while network coding showed better performance than MH routing in terms of reducing transmission power. MH networking has further been investigated in other simple but realistic network conditions that take into account the practical issues of coding and delay [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A recent result [4] has shown that an almost linear throughput in the network, i.e., Θ(n 1− ) for an arbitrarily small > 0, is achievable by using a hierarchical cooperation (HC) strategy. 2 Along with the studies in terrestrial radio networks, the interest in study of underwater networks has been growing [5], [6], due to recent advances in acoustic communication technology. In underwater acoustic communication systems, both bandwidth and received signal power can be severely limited owing to exponential (rather than polynomial) pathloss attenuation with propagation distance and frequencydependent attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the studies in terrestrial radio networks, the interest in study of underwater networks has been growing with recent advances in acoustic communication technology [5], [6]. In underwater acoustic communication systems, both bandwidth and power are severely limited due to the exponential (rather than polynomial) path-loss attenuation with This work was supported in part by the National Science Foundation under grants No.…”
Section: Introductionmentioning
confidence: 99%
“…This is a main feature that distinguishes underwater systems from wireless radio links. Based on these characteristics, network coding schemes [6]- [8] have been presented for underwater acoustic channels. One natural question is what are the fundamental capabilities of underwater networks in supporting multiple S-D pairs over an acoustic channel.…”
Section: Introductionmentioning
confidence: 99%